Composite molecular sieve as well as preparation method and application thereof
By using small-grain mordenite/β zeolite composite molecular sieve and weak hydrogenation function deolefin catalysts, combined with rare earth metals, the problems of long steps of heavy aromatic hydrocarbon treatment process above C10 and poor catalyst activity stability in the prior art are solved, and efficient heavy aromatic hydrocarbon conversion and high-value utilization are achieved.
Patent Information
- Application Number
- CN202311734684.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2025-06-17
AI Technical Summary
When the prior art treats heavy aromatic hydrocarbons above C10, the process steps are long, the hydrogen consumption is high, the catalyst activity stability is poor, and high value utilization cannot be achieved.
Small-grain mordenite/β-zeolite composite molecular sieve is used as the catalyst support, combining weak hydrogenation function deolefins and composite molecular sieve alkyl transfer catalysts to achieve ring-opening cracking and alkyl transfer of heavy aromatic hydrocarbons, reduce aromatic hydrocarbon losses, improve methyl utilization, and improve the life and stability of the catalyst by adding rare earth metals.
The aromatic hydrocarbon loss rate is reduced, the methyl utilization rate of heavy aromatic hydrocarbons and the stability of catalysts are improved, and the conversion rate of aromatic hydrocarbon fractions above C10 and selectivity of aromatic products are enhanced.
Smart Images

Figure CN120157150A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of catalysts, and particularly relates to a composite molecular sieve, a preparation method thereof, and an application thereof. Background Art
[0002] Under the condition of the action of a catalyst, the process of rearranging the molecular structure of hydrocarbon molecules in gasoline fractions to form a new molecular structure is called catalytic reforming. The aromatic hydrocarbon components remaining after the heavy aromatics by-produced in catalytic reforming are rectified to extract carbon nine (containing a small amount of carbon ten) are mostly used as low-value fuels except for a small part used for producing aromatic hydrocarbon solvent oil or gasoline blending components, with low raw material utilization rate and difficult to comprehensively utilize the potential economic value of polycyclic aromatic hydrocarbons in heavy aromatic hydrocarbon raw materials.
[0003] An existing method for hydro-upgrading of heavy aromatics is to carry out two-step hydrogenation, and pre-hydrogenation saturation and hydrocracking reactions are respectively carried out through two series-connected reactors in sequence; the reaction products are separated by one-step rectification to obtain a mixture of benzene, toluene and low-carbon alkanes, and the bottom material of the tower is further rectified to separate C8-C9. The crude aromatic hydrocarbon product or the light fraction before 205°C is used as a blending component for high-octane gasoline, and the bottom heavy fraction is recycled for reaction. This method can be used to process the heavy deca-aromatics by-produced in the catalytic reforming unit or steam cracking unit of a refinery to increase the production of high-value light aromatics or high-octane gasoline blending components. However, this method faces problems such as long process steps, high hydrogen consumption caused by two-step hydrogenation, and poor activity stability of the reaction catalyst.
[0004] The existing process generally uses a reactor filled with a catalyst loaded with platinum or a low-hydrogen type binderless ten-membered ring zeolite catalyst. Under the reaction conditions of a reaction temperature of 380 - 420°C, a pressure of 2.4 - 3.5 Mpa, a weight hourly space velocity of 1 - 3 h -1 and a hydrogen-hydrocarbon molar ratio of 4 - 8:1, selectively hydrocracks C9 aromatics except trimethylbenzene to increase the production of BTX (a mixture of three isomers of benzene, toluene and xylene), and separates the trimethylbenzene product from the product. This process has good conversion activity and value-added significance for heavy aromatics mainly composed of C9, but is limited by the pore size of the molecular sieve used and is not suitable for the hydrotreatment of heavy aromatics with more than C10, and cannot realize the high-value utilization of heavy aromatics with more than C10. Summary of the Invention
[0005] In order to overcome the defects existing in the above-mentioned prior art, the purpose of this application is to provide a composite molecular sieve, a preparation method thereof, and an application thereof, by preparing a composite molecular sieve with small crystal grains and high activity for catalytic production of BTX, thereby reducing the aromatic hydrocarbon loss rate, improving the product selectivity, and enhancing the stability of the catalyst.
[0006] To achieve the above purpose, this application provides the following technical solutions:
[0007] A preparation method of a composite molecular sieve, comprising:
[0008] Prepare an initial solution by mixing a silicon source, an aluminum source, a template agent, an alkali source and seeds according to a ratio.
[0009] Adjust the pH value of the initial solution and perform hydrothermal crystallization to obtain a composite molecular sieve with a grain diameter of 0.001 - 10 microns.
[0010] Further, adjust the pH value of the initial solution to 9 - 14.
[0011] Further, the temperature of hydrothermal crystallization is 100 - 200 °C, and the time of hydrothermal crystallization is 10 - 100 hours.
[0012] Further, the silicon source includes at least one of silicate, silicate or silicon oxide sol;
[0013] The aluminum source includes at least one of aluminate or aluminum salt;
[0014] The template agent includes at least one of ethylenediamine, ethylamine, triethylamine, n - butylamine, inorganic ammonia, tetrapropylammonium halide or tetrapropylammonium hydroxide;
[0015] The alkali source includes NaOH;
[0016] The seeds include amorphous substances with grains of 1 - 200 nanometers containing β - zeolite and mordenite precursors, and the molar ratio of SiO2 / Al2O3 in the seeds is 30 - 100:1.
[0017] Further, the molar ratio of the initial solution is SiO2∶Al2O3∶Na2O∶template agent∶H2O∶seeds = 1:0.001 - 0.1:0.01 - 0.3:0.05 - 0.6:30 - 200:0.005 - 0.2,
[0018] wherein, the molecular weight of the seeds is calculated based on the molecular weight of SiO2.
[0019] In a second aspect, the present application discloses a composite molecular sieve prepared by the method described in the above claims. The grain diameter of the composite molecular sieve is 0.001 - 10 microns.
[0020] In a third aspect, the present application discloses a catalyst prepared by using the above - mentioned composite molecular sieve. The content of the composite molecular sieve in the catalyst is 60 - 80%, the content of the active metal oxide is 1.0 - 10%, the content of the binder is 30 - 45%, and the content of the promoter in the catalyst is 0.2 - 5%.
[0021] Further, the active metal oxide is separately loaded on the binder.
[0022] Further, the elemental types of the cocatalyst include one or two of palladium, platinum, ruthenium, iridium, gold, antimony, or rhenium, and one or two of transition metals tantalum, nickel, cobalt, zirconium, molybdenum, lanthanum, manganese, vanadium, iron, cadmium, or niobium.
[0023] Further, the binder includes one or more of silica sol, diatomite, alumina, natural bentonite, and titanium oxide.
[0024] Fourthly, the present application discloses an application of a catalyst, which is based on the above catalyst and is used for producing BTX from heavy aromatics.
[0025] Further, the heavy aromatics include aromatic fractions with more than C10 by-products from refinery reforming units or steam cracking units.
[0026] Further, the process conditions for producing BTX from heavy aromatics are as follows: the reaction hydrogen pressure is 1 - 3 MPa, the hydrogen-hydrocarbon molar ratio is 3 - 6, the reaction temperature is 340 - 420 °C, and the weight hourly space velocity is 1.0 - 5.0 h -1 .
[0027] Further, the application also includes evaluating the performance of the catalyst based on the single-pass conversion rate of aromatic fractions with more than C10 and the selectivity of benzene, xylene, and C9 aromatics;
[0028] The calculation formula for the single-pass conversion rate of aromatic fractions with more than C10 is as follows:
[0029]
[0030] Among them, X(PAHs) is the single-pass conversion rate of aromatic fractions with more than C10, and w(PAHs) F is the mass fraction of aromatic fractions with more than C10 in the raw material, and w(PAHs) P is the mass fraction of aromatic fractions with more than C10 in the product;
[0031] The calculation formulas for the selectivity of benzene, xylene, and C9 aromatics are as follows:
[0032]
[0033] Y(B + C8~9A) is the yield of benzene, xylene, and C9 aromatics, and w(B) P is the mass fraction of benzene in the product, and w(B) F is the mass fraction of benzene in the raw material, and w(C8~9A) P is the sum of the mass fractions of carbon eight and carbon nine in the product, and w(C8~9A) F is the sum of the mass fractions of carbon eight and carbon nine in the raw material, and w(T) F is the mass fraction of toluene in the raw material, and w(T) Pis the mass fraction of toluene in the product, w(PAHs) F is the mass fraction of aromatic hydrocarbon fractions with more than C10 in the raw material, w(PAHs) P is the mass fraction of aromatic hydrocarbon fractions with more than C10 in the product.
[0034] Technical effects and advantages of this application:
[0035] 1. By providing a preparation method of small crystal mordenite / β zeolite composite molecular sieve, this application solves the problems in the prior art that the synthesized composite molecular sieve has large crystal grains, low catalytic activity, is prone to coking during the heavy aromatic hydrocarbon reaction process, the catalyst deactivates quickly, and the product yield is low.
[0036] 2. This application adopts the combined technology of deolefin with weak hydrogenation function and composite molecular sieve alkyl transfer catalyst to realize the ring-opening cracking and alkyl transfer of heavy aromatic hydrocarbons, reduce aromatic hydrocarbon loss, improve the methyl utilization rate of heavy aromatic hydrocarbons, and extend the catalyst life.
[0037] 3. This application uses small crystal mordenite and β zeolite as carriers. Among them, mordenite is suitable for the diffusion of large aromatic hydrocarbon molecules and the occurrence of alkyl transfer reactions. β zeolite has strong acidity and is suitable for the removal of alkyl groups and the hydrogenation cracking of polycyclic aromatic hydrocarbon components in combination with precious metals. By adding rare earth metals to the catalyst, the life and stability of the catalyst are improved, and the conversion rate of heavy aromatic hydrocarbons and the selectivity of aromatic hydrocarbon products are generally improved.
[0038] Other features and advantages of this application will be described in the subsequent specification, and part of them will be obvious from the specification or understood by implementing this application. The objectives and other advantages of this application can be realized and obtained through the structures pointed out in the specification, claims, and drawings. Brief Description of the Drawings
[0039] Figure 1 is a flow chart of a preparation method of a composite molecular sieve of this application. Detailed Embodiments
[0040] Next, the technical solutions in the embodiments of this application will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, rather than all the embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of this application.
[0041] As Figure 1 shown, this application provides a preparation method of a composite molecular sieve, including:
[0042] Prepare a solution by mixing a silicon source, an aluminum source, a template agent, an alkali source, and seeds according to a ratio;
[0043] Adjust the pH value of the initial solution and perform hydrothermal crystallization to obtain a composite molecular sieve with a grain diameter of 0.001 - 10 μm, preferably a grain diameter of 0.01 - 4 μm, and more preferably a grain diameter of 0.1 - 2 μm.
[0044] In some embodiments of the present application, the pH value of the initial solution is adjusted to 9 - 14 (such as 9, 10, 11, 12, 13, or 14), and preferably the pH value is 10.5 - 13.5.
[0045] In some embodiments of the present application, the temperature of hydrothermal crystallization is 100 - 200 °C (such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, or 200 °C, preferably 120 - 160 °C), and the time of hydrothermal crystallization is 10 - 100 hours (such as 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100 hours, preferably 10 - 40 hours).
[0046] In some embodiments of the present application, the silicon source includes at least one of silicate, silicate, or silicon oxide sol;
[0047] The aluminum source includes at least one of aluminate or aluminum salt;
[0048] The template agent includes at least one of ethylenediamine, ethylamine, triethylamine, n - butylamine, inorganic ammonia, tetrapropylammonium halide, or tetrapropylammonium hydroxide;
[0049] The base source includes NaOH;
[0050] The seed crystal includes an amorphous substance with grains of β - zeolite and mordenite precursors in the range of 1 - 200 nm, preferably an amorphous substance with grains in the range of 1 - 100 nm, and the molar ratio of SiO2 / Al2O3 in the seed crystal is 30 - 100:1, such as 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, or 100:1.
[0051] It should be noted that the present application uses small - grain mordenite and β - zeolite as carriers. Among them, mordenite is suitable for the diffusion of large - molecule aromatics and the occurrence of alkyl transfer reactions. β - zeolite has strong acidity and is suitable for the removal of alkyl groups and the hydrocracking of polycyclic aromatic components in combination with noble metals.
[0052] In some embodiments of the present application, the molar ratio of the solution is SiO2∶Al2O3∶Na2O∶template agent∶H2O∶seed crystal = 1:(0.001 - 0.1):(0.01 - 0.3):(0.05 - 0.6):(30 - 200):(0.005 - 0.2), preferably 1:(0.025 - 0.083):(0.025 - 0.2):(0.1 - 0.4):(40 - 100):(0.01 - 0.1).
[0053] Among them, the molecular weight of the seed crystal is calculated based on the molecular weight of SiO2.
[0054] In a second aspect, the present application discloses a composite molecular sieve prepared by the above method. The crystal grain diameter of the composite molecular sieve is 0.001 - 10 microns. The composite molecular sieve includes mordenite molecular sieve and β zeolite molecular sieve. By weight percentage, the content of mordenite molecular sieve in the composite molecular sieve is 1 - 99%, preferably 50 - 80%. The SiO2 / Al2O3 molar ratio range of the composite molecular sieve is 12 - 40:1.
[0055] In a third aspect, the present application discloses a catalyst prepared by using the above composite molecular sieve. The content of the composite molecular sieve in the catalyst is 60 - 80%, the content of the active metal oxide is 1.0 - 10%, the content of the binder is 30 - 45%, and the content of the cocatalyst in the catalyst is 0.2 - 5%.
[0056] In some embodiments of the present application, the active metal oxide is separately loaded on the binder.
[0057] In some embodiments of the present application, the elemental types of the cocatalyst include one or two of palladium, platinum, ruthenium, iridium, gold, antimony or rhenium, and one or two of transition metals tantalum, nickel, cobalt, zirconium, molybdenum, lanthanum, manganese, vanadium, iron, cadmium or niobium.
[0058] By adding rare earth metals to the catalyst, the service life and stability of the catalyst can be improved.
[0059] In some embodiments of the present application, the binder includes one or more of silica sol, diatomite, alumina, natural bentonite, and titanium oxide.
[0060] In a fourth aspect, the present application discloses an application of a catalyst. Based on the above catalyst, the production of BTX from heavy aromatics is realized, and the single-pass conversion rate of aromatics fraction above C10 > 60%; the selectivity of benzene, xylene and C9 aromatics is 88 - 92%.
[0061] In some embodiments of the present application, the heavy aromatics include aromatics fraction above C10 produced as a by-product in a refinery reforming unit or a steam cracking unit.
[0062] In some embodiments of the present application, the process conditions for producing BTX from heavy aromatics are as follows: the reaction hydrogen pressure is 1 - 3 MPa, the hydrogen-hydrocarbon molar ratio is 3 - 6, the reaction temperature is 340 - 420 °C, and the weight hourly space velocity is 1.0 - 5.0 h -1 .
[0063] In some embodiments of the present application, the calculation formula for the single-pass conversion rate of aromatics fractions with 10 or more carbon atoms is as follows: The calculation formula for the single-pass conversion rate of aromatics fractions with 10 or more carbon atoms is as follows:
[0064]
[0065] Wherein, X(PAHs) is the single-pass conversion rate of aromatics fractions with 10 or more carbon atoms, w(PAHs) F is the mass fraction of aromatics fractions with 10 or more carbon atoms in the raw material, w(PAHs) P is the mass fraction of aromatics fractions with 10 or more carbon atoms in the product;
[0066] The calculation formulas for the selectivities of benzene, xylene, and C9 aromatics are as follows:
[0067]
[0068] Y(B + C8-9A) is the yield of benzene, xylene, and C9 aromatics, w(B) P is the mass fraction of benzene in the product, w(B) F is the mass fraction of benzene in the raw material, w(C8-9A) P is the sum of the mass fractions of carbon eight and carbon nine in the product, w(C8-9A) F is the sum of the mass fractions of carbon eight and carbon nine in the raw material, w(T) F is the mass fraction of toluene in the raw material, w(T) P is the mass fraction of toluene in the product, w(PAHs) F is the mass fraction of aromatics fractions with 10 or more carbon atoms in the raw material, w(PAHs) P is the mass fraction of aromatics fractions with 10 or more carbon atoms in the product.
[0069] To better illustrate the present solution, the following examples are also provided. In the raw materials used in the following examples, sodium hydroxide is used to provide the sodium source, and dilute acid is used to adjust the pH value of the sol. All the reagents used are commercially available chemically pure reagents, and the SiO2 content in the silica sol is 40 wt%.
[0070] Example 1
[0071] Dissolve 1137 g of sodium metasilicate in 1800 g of deionized water. Separately, dissolve 89 g of aluminum sulfate in 350 g of deionized water and add it to the previous solution under stirring. After the solutions are mixed evenly, add 100 g of ethylenediamine under stirring. After stirring evenly, adjust the pH value to 10.5 with 30% sulfuric acid solution, then continue stirring until homogeneous. Carry out conventional hydrothermal crystallization at 160 °C for 15 hours. After washing the crystallization product, dry it at 130 °C for 4 hours and calcine it at 550 °C for 3 hours to obtain the seed crystal, denoted as M1. By weight percentage, the proportion of β-zeolite and mordenite precursor in the seed crystal is about 60%.
[0072] Dissolve 540 g of silica sol in 3000 g of deionized water. Add 240 mL of 3 mol / L sodium hydroxide solution under stirring until homogeneous. Then dissolve 28.8 g of sodium aluminate in 1800 mL of deionized water and add it to the previous solution and stir until homogeneous. Then add 96 g of n-butylamine and 22 g of seed crystal M1 under stirring to obtain the initial solution. The molar ratio of the components of the initial solution is: SiO2∶Al2O3∶Na2O∶n-butylamine∶H2O∶M1 = 1∶0.049∶0.1∶0.36∶82∶0.1. Adjust the pH value of the initial solution to 11.5 with dilute sulfuric acid. After stirring evenly, carry out conventional hydrothermal crystallization at 160 °C for 30 hours. After filtering and washing the crystallization product, dry it at 130 °C for 3 hours and then calcine it at 550 °C for 5 hours to obtain the composite molecular sieve (mass ratio of mordenite to β-zeolite = 80:20).
[0073] Dissolve ammonium heptamolybdate and bismuth nitrate in nitric acid to prepare the first solution (the mass concentration of HNO3 in the first solution is 3%). Mix the composite molecular sieve and pseudoboehmite in a mass ratio of 80:20 and add them to the first solution. After kneading evenly, extrude them into cylindrical bars with a diameter of 2.0 mm, place them in the air for 6 hours, and dry them at 120 °C for 2 hours to obtain the catalyst precursor. Immerse the catalyst precursor in a solution containing chloroplatinic acid, then dry it in the air at 130 °C for 2.5 hours and calcine it at 550 °C for 2 hours to obtain the oxidized catalyst with a molybdenum content of 3 wt%, a bismuth content of 0.2 wt%, and a platinum content of 0.01 wt%. Finally, reduce the oxidized catalyst in hydrogen at 500 °C for 4 hours to obtain catalyst A1. Use catalyst A1 to produce BTX from heavy aromatics. React under the conditions of a reaction temperature of 375 °C, a hydrogen partial pressure of 2.5 MPa, a feed space velocity of 3 h -1 and a hydrogen-hydrocarbon molar ratio of 5.0. The properties of the heavy aromatics as the raw material are shown in Table 1, and the corresponding conversion performance of catalyst A1 is shown in Table 2. The single-pass conversion rate of the C10+ aromatic hydrocarbon fraction is 64.8%, the selectivity for benzene, xylene, and C9 aromatics is 91.3%, and the aromatic hydrocarbon loss rate is 1.3%.
[0074] Example 2
[0075] Change the addition amount of sodium aluminate in Example 1 to 39.4 g, adjust the initial solution pH value to 13.5, and prepare the composite molecular sieve according to the molar ratio of SiO2∶Al2O3∶Na2O∶template agent∶H2O∶seed crystal = 1:0.067:0.1:0.36:82:0.1, with other conditions unchanged.
[0076] Dissolve ammonium heptamolybdate and bismuth nitrate in nitric acid to obtain the first solution (the mass concentration of HNO3 in the first solution is 3%). Mix the composite molecular sieve and pseudo-boehmite in a mass ratio of 80:20, add them to the first solution, knead evenly, extrude into cylindrical bars with a diameter of 2.0 mm, place them in the air for 6 hours, and dry them at 120 °C for 2 hours to obtain the catalyst precursor. Immerse the catalyst precursor in a solution containing chloroplatinic acid, then dry it in the air at 130 °C for 2.5 hours and calcine it at 550 °C for 2 hours to obtain an oxidized catalyst with a molybdenum content of 3 wt%, a bismuth content of 0.2 wt%, and a platinum content of 0.01 wt%. Finally, reduce the oxidized catalyst in hydrogen at 500 °C for 4 hours to obtain Catalyst A1. Use Catalyst A1 to produce BTX from heavy aromatics. React under the conditions of a reaction temperature of 375 °C, a hydrogen partial pressure of 2.5 MPa, a feed space velocity of 3 h -1 React under the condition of a hydrogen-hydrocarbon molar ratio of 5.0. The properties of the heavy aromatics as the raw material are shown in Table 1, and the corresponding conversion performance of Catalyst A1 is shown in Table 2. The single-pass conversion rate of the aromatic hydrocarbon fraction above C10 is 63.4%, the selectivity for benzene, xylene, and C9 aromatics is 89.7%, and the aromatic hydrocarbon loss rate is 1.2%.
[0077] Example 3
[0078] Change the addition amount of sodium aluminate in Example 1 to 19.7 g, adjust the initial solution pH value to 13.5, and prepare the composite molecular sieve according to the molar ratio of SiO2∶Al2O3∶Na2O∶template agent∶H2O∶seed crystal = 1:0.033:0.1:0.36:82:0.1, with other conditions unchanged.
[0079] Place the composite molecular sieve in an aqueous solution of ammonium chloride, perform ion exchange at 90 °C for 6 hours, filter off the mother liquor, repeat the ion exchange 2 - 4 times, wash it, and dry it at 120 °C for 2 hours to obtain the mixed ammonium-type zeolite.
[0080] Ammonium heptamolybdate and bismuth nitrate were dissolved in nitric acid to prepare a first solution (the mass concentration of HNO3 in the first solution was 3%). The composite molecular sieve and pseudoboehmite were mixed at a mass ratio of 80:20 and added to the first solution. After kneading evenly, it was extruded into cylindrical bars with a diameter of 2.0 mm, placed in air for 6 hours, and dried at 120 °C for 2 hours to obtain a catalyst precursor. The catalyst precursor was impregnated in a solution containing chloroplatinic acid, then dried in air at 130 °C for 2.5 hours and calcined at 550 °C for 2 hours to obtain an oxidized catalyst with a molybdenum content of 3 wt%, a bismuth content of 0.2 wt%, and a platinum content of 0.01 wt%. Finally, the oxidized catalyst was reduced in hydrogen at 500 °C for 4 hours to obtain catalyst A1. Catalyst A1 was used to produce BTX from heavy aromatics. The reaction was carried out under the conditions of a reaction temperature of 375 °C, a hydrogen partial pressure of 2.5 MPa, a feed space velocity of 3 h-1, and a hydrogen-hydrocarbon molar ratio of 5.0. The properties of the heavy aromatics as the raw material are shown in Table 1, and the corresponding conversion performance of catalyst A1 is shown in Table 2. The single-pass conversion rate of the aromatic fraction above C10 was 63.4%, the selectivity for benzene, xylene, and C9 aromatics was 89.7%, and the aromatic loss rate was 1.2%.
[0081] Example 4
[0082] The composite molecular sieve prepared in Example 1 (the mass ratio of mordenite to β-zeolite = 80:20) was placed in an aqueous solution of ammonium chloride and ion-exchanged at 90 °C for 6 hours. The mother liquor was filtered off, and the ion-exchange was repeated 2 - 4 times. After washing, it was dried at 120 °C for 2 hours to obtain a mixed ammonium-type zeolite.
[0083] Ammonium heptamolybdate and bismuth nitrate were dissolved in nitric acid to prepare a first solution (the mass concentration of HNO3 in the first solution was 3%). The mixed ammonium-type zeolite and pseudoboehmite were mixed at a mass ratio of 80:20 and added to the first solution. After kneading evenly, it was extruded into cylindrical bars with a diameter of 2.0 mm, placed in air for 6 hours, and dried at 120 °C for 2 hours to obtain a catalyst precursor. The catalyst precursor was impregnated in a solution containing chloroplatinic acid, then dried in air at 130 °C for 2.5 hours and calcined at 550 °C for 2 hours to obtain an oxidized catalyst with a molybdenum content of 3 wt%, a bismuth content of 0.2 wt%, and a platinum content of 0.01 wt%. Finally, the oxidized catalyst was reduced in hydrogen at 500 °C for 4 hours to obtain catalyst A1. Catalyst A1 was used to produce BTX from heavy aromatics. The reaction was carried out under the conditions of a reaction temperature of 375 °C, a hydrogen partial pressure of 2.5 MPa, a feed space velocity of 3 h -1 -1, and a hydrogen-hydrocarbon molar ratio of 5.0. The properties of the heavy aromatics as the raw material are shown in Table 1, and the corresponding conversion performance of catalyst A1 is shown in Table 2. The single-pass conversion rate of the aromatic fraction above C10 was 67.8%, the selectivity for benzene, xylene, and C9 aromatics was 88.1%, and the aromatic loss rate was 2.3%.
[0084] Example 5
[0085] After preparing the composite molecular sieve (the mass ratio of mordenite to β-zeolite = 60:40) according to the method of Example 1, it was placed in an aqueous solution of ammonium chloride, ion-exchanged at 90 °C for 6 hours, the mother liquor was filtered off, the ion-exchange was repeated 2 - 4 times, washed and then dried at 120 °C for 2 hours to obtain a mixed ammonium-type zeolite.
[0086] Nickel nitrate and lanthanum nitrate were dissolved in nitric acid to prepare a first solution (the mass concentration of HNO3 in the first solution was 3%). The mixed ammonium-type zeolite and pseudoboehmite were mixed (the mass ratio of mixed zeolite / pseudoboehmite = 80:20), and the above first solution was added. After kneading evenly, it was extruded into cylindrical bars with a diameter of 2.0 mm, placed in air for 6 hours, and dried at 120 °C for 2 hours to obtain a catalyst precursor. The catalyst precursor was impregnated in a solution containing palladium chloride, then dried in air at 130 °C for 2.5 hours and calcined at 550 °C for 2 hours to obtain an oxidized catalyst with a nickel content of 3 wt%, a lanthanum content of 0.2 wt%, and a palladium content of 0.01 wt%. Finally, the oxidized catalyst was reduced in hydrogen at 500 °C for 4 hours to obtain Catalyst A1. Under the reaction conditions of a reaction temperature of 375 °C, a hydrogen partial pressure of 2.5 MPa, a feed space velocity of 3 h -1 and a hydrogen-hydrocarbon molar ratio of 5.0. The properties of the heavy aromatics as the raw material are shown in Table 1, and the corresponding conversion performance of Catalyst A1 is shown in Table 2. The single-pass conversion rate of the aromatics fraction with C10 and above is 63.8%, the selectivity for benzene, xylene, and C9 aromatics is 88.1%, and the aromatic loss rate is 2.4%.
[0087] Example 6
[0088] After preparing the composite molecular sieve (the mass ratio of mordenite to β-zeolite = 60:40) according to the method of Example 1, it was placed in an aqueous solution of ammonium chloride, ion-exchanged at 90 °C for 6 hours, the mother liquor was filtered off, the ion-exchange was repeated 2 - 4 times, washed and then dried at 120 °C for 2 hours to obtain a mixed ammonium-type zeolite.
[0089] Ammonium heptamolybdate and bismuth nitrate were dissolved in nitric acid to prepare a first solution (the mass concentration of HNO3 in the first solution was 3%). The mixed ammonium-type zeolite and pseudoboehmite were mixed (the mass ratio of mixed zeolite / pseudoboehmite = 70:30), and the above-mentioned first solution was added. After kneading evenly, it was extruded into cylindrical bars with a diameter of 2.0 mm, placed in air for 6 hours, and dried at 120 °C for 2 hours to obtain a catalyst precursor. The catalyst precursor was impregnated in a solution containing chloroplatinic acid, then dried in air at 130 °C for 2.5 hours and calcined at 550 °C for 2 hours to obtain an oxidized catalyst with a molybdenum content of 5 wt%, a bismuth content of 0.8 wt%, and a platinum content of 0.03 wt%. Finally, the oxidized catalyst was reduced in hydrogen at 500 °C for 4 hours to obtain catalyst A1. It was reacted under the conditions of a reaction temperature of 375 °C, a hydrogen partial pressure of 2.5 MPa, a feed space velocity of 3 h -1 -1, and a hydrogen-hydrocarbon molar ratio of 5.0. The properties of the heavy aromatics as the raw material are shown in Table 1, and the corresponding conversion performance of catalyst A1 is shown in Table 2. The single-pass conversion rate of the aromatic hydrocarbon fraction with 10 or more carbon atoms is 70.3%, the selectivity for benzene, xylene, and C9 aromatics is 89.1%, and the aromatic hydrocarbon loss rate is 4.2%.
[0090] Table 1 Raw material properties
[0091] Item Analysis result Bromine index, mgBr / 100g 1500 Distillation range HK, °C 176.1 Distillation range, 50% °C 185.2 Distillation range, KK °C 329.1 <![CDATA[Density, g / cm 3 > 0.9146 Content of polycyclic aromatic hydrocarbons above two rings, % >51
[0092] Table 2 Corresponding conversion performance of the examples
[0093]
[0094] Finally, it should be noted that the above are only the preferred embodiments of the present application and are not used to limit the present application. Although the present application has been described in detail with reference to the foregoing embodiments, for those skilled in the art, they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included within the protection scope of the present application.
Claims
1. A method for preparing a composite molecular sieve, characterized in that, Comprising: Preparing an initial solution by mixing a silicon source, an aluminum source, a template agent, an alkali source and seeds according to a ratio; Adjusting the pH value of the initial solution and performing hydrothermal crystallization to obtain a composite molecular sieve with a grain diameter of 0.001 - 10 microns.
2. The method for preparing a composite molecular sieve according to claim 1, characterized in that, Adjusting the pH value of the initial solution to 9 - 14.
3. The method for preparing a composite molecular sieve according to claim 1, characterized in that, The temperature of the hydrothermal crystallization is 100 - 200 °C, and the time of the hydrothermal crystallization is 10 - 100 hours.
4. The method for preparing a composite molecular sieve according to claim 1, characterized in that, The silicon source includes at least one of silicate, silicate or silicon oxide sol; The aluminum source includes at least one of aluminate or aluminum salt; The template agent includes at least one of ethylenediamine, ethylamine, triethylamine, n-butylamine, inorganic ammonia, tetrapropylammonium halide or tetrapropylammonium hydroxide; The alkali source includes NaOH; The seeds include an amorphous substance with a grain size of 1 - 200 nm containing β-zeolite and mordenite precursors, and the molar ratio of SiO2 / Al2O3 in the seeds is 30 - 100:
1.
5. The method for preparing a composite molecular sieve according to claim 1, characterized in that, The molar ratio of the initial solution is SiO2∶Al2O3∶Na2O∶template agent∶H2O∶seeds = 1:0.001 - 0.1:0.01 - 0.3:0.05 - 0.6:30 - 200:0.005 - 0.2, wherein, the molecular weight of the seeds is calculated based on the molecular weight of SiO2.
6. A composite molecular sieve, characterized in that, The composite molecular sieve is prepared by the method according to any one of claims 1 - 5, and the grain diameter of the composite molecular sieve is 0.001 - 10 microns.
7. A catalyst, characterized in that, The catalyst is prepared by using a composite molecular sieve according to claim 6. The content of the composite molecular sieve in the catalyst is 60 - 80%, the content of the active metal oxide is 1.0 - 10%, the content of the binder is 30 - 45%, and the content of the promoter in the catalyst is 0.2 - 5%.
8. The catalyst according to claim 7, characterized in that, The active metal oxide is separately loaded on the binder.
9. The catalyst according to claim 7, characterized in that, The elemental types of the promoter include one or two of palladium, platinum, ruthenium, iridium, gold, antimony or rhenium, and one or two of transition metals tantalum, nickel, cobalt, zirconium, molybdenum, lanthanum, manganese, vanadium, iron, cadmium or niobium.
10. The catalyst according to claim 7, characterized in that, The binder includes one or more of silica sol, diatomite, alumina, natural bentonite, titanium oxide.
11. An application of a catalyst, characterized in that, The application is based on the catalyst according to any one of claims 7 - 10 and is used for producing BTX from heavy aromatics.
12. The application of a catalyst according to claim 11, characterized in that, The heavy aromatics include aromatic fractions with more than C10 by-products from refinery reforming units or steam cracking units.
13. The application of a catalyst according to claim 11, characterized in that, The process conditions for producing BTX from heavy aromatics are as follows: the reaction hydrogen pressure is 1 - 3 MPa, the hydrogen-hydrocarbon molar ratio is 3 - 6, the reaction temperature is 340 - 420 °C, and the weight hourly space velocity is 1.0 - 5.0 h -1 .
14. The application of a catalyst according to claim 11, characterized in that, The application further includes evaluating the performance of the catalyst based on the single-pass conversion rate of aromatic fractions with more than C10 and the selectivity of benzene, xylene and C9 aromatics; The calculation formula for the single-pass conversion rate of aromatic fractions with more than C10 is as follows: Among them, X(PAHs) is the single-pass conversion rate of the aromatic hydrocarbon fraction with more than C10, and w(PAHs) F is the mass fraction of the aromatic hydrocarbon fraction with more than C10 in the raw material, and w(PAHs) P is the mass fraction of the aromatic hydrocarbon fraction with more than C10 in the product; The calculation formula for the selectivity of benzene, xylene and C9 aromatics is as follows: Y(B + C8~9A) is the yield of benzene, xylene and C9 aromatics, w(B) P is the mass fraction of benzene in the product, w(B) F is the mass fraction of benzene in the feedstock, w(C8~9A) P is the sum of the mass fractions of C8 and C9 in the product, w(C8~9A) F is the sum of the mass fractions of C8 and C9 in the feedstock, w(T) F is the mass fraction of toluene in the feedstock, w(T) P is the mass fraction of toluene in the product, w(PAHs) F is the mass fraction of aromatic fractions above C10 in the feedstock, w(PAHs) P is the mass fraction of aromatic fractions above C10 in the product.